Association of chondroadherin with leiomyosarcoma - Sefik Gokce; Dilsad Herkiloglu; Ecmel İsik Kaygusuz; Ozge Cevik; Sarfraz Ahmad (Gynecologic Oncology Reports, 2023)
The leiomyosarcoma (LMS) subtype of uterine sarcoma accounts for 1–2 % of uterine neoplasia cases. The present study aimed to demonstrate that the gene and protein chondroadherin (CHAD) levels may serve as novel biomarkers for predicting prognosis and devising novel treatment models for LMS. A total of 12 patients diagnosed with LMS and 13 patients diagnosed with myomas were included in the study. The extent of tumour cell necrosis, cellularity and atypia and the mitotic index of each patient with LMS were determined. CHAD gene expression was significantly increased in cancerous tissues compared with that in fibroid tissues (2.17 ± 0.88 vs 3.19 ± 1.61; P = 0.047). The mean CHAD protein expression in tissues was higher in LMS cases but this was not statistically significant (217.38 ± 93.9 vs 177.13 ± 66.67;P = 0.226). Positive significant correlations were obtained between CHAD gene expression and mitotic index (r = 0.476; P = 0.008), tumour size (r = 0.385; P = 0.029) and necrosis (r = 0.455; P = 0.011). Furthermore, there were significant positive correlations between CHAD protein expression levels and tumour size (r = 0.360; P = 0.039) and necrosis (r = 0.377; P = 0.032). The present study was the first to demonstrate the significance of CHAD in LMS. The results suggested that, due to its association with LMS, CHAD has predictive value in determining the prognosis of patients with LMS.